Family Centred Care: A Descriptive Study of the Situation in Rural Western Australia - Wilson, Sally B. (Curtin University, 2004)
Family centred care is a concept espoused to be fundamental to achieving excellence in paediatric nursing. Although it is recognised that family centred care includes the child's rights to self determination the focus of this study is parental participation in the decision making and care of their hospitalised child at a partnership level. This is based on negotiation and requires frequent, effective communication between parents and nurses and for each to respect the other's knowledge and appreciate the other has something to offer in the relationship which will benefit the child. The purpose of this study was to identify whether family centred care was occurring in paediatric settings in rural Western Australia and explored parents' and nurses' perceptions of the concept. A questionnaire was designed based on the literature and common themes identified from focus groups. Convenience sampling was used and 15 rural hospitals facilitated participation of 243 parents who had a child under ten years of age hospitalised and 108 nurses who cared for children. Exploratory factor analysis identified four subscales from the parents' questionnaire and three subscales from the nurses' questionnaire which measured separate concepts of family centred care. Descriptive statistics were generated for each subscale, and independent t-tests, ANOVA and correlations were examined between independent variables and subscales of family centred care. There was a statistically significant difference in scores for parents' perceptions of `child friendly environment' between regional and district hospitals. Those parents who did not have social support scored a statistically significantly lower mean score for `respect as parent'. Nurses in district hospitals generated statistically significantly higher mean scores for `family focussed hospital' than those who worked in regional hospitals.Parents and nurses both perceived that parents wanted to continue parenting their hospitalised child, however parents wanted to provide more nursing care than was perceived by nurses. Nurses' perceptions of delivering family centred care were greater than the perceptions of parents receiving it, however they were consistent in items that were scored low. Nurses did ask parents about the amount of participation they wanted in their child's care on admission however, it was not done on a regular basis. Parents perceived that nurses were unaware of other things that parents needed to attend to while their child was hospitalised and therefore did not enable parents to attend to these needs. More frequent negotiation of roles between parents and nurses by communicating each shift, or at least daily, could narrow the gap between differing perceptions in care provision and also enable parents to attend to their other roles thereby reducing their levels of physical and emotional stress.